Holocene matters: Landscape history accounts for current species richness of vascular plants in forests and grasslands of eastern Central Europe. (23rd January 2020) - Divíšek, Jan; Hájek, Michal; Jamrichová, Eva; Petr, Libor; Večeřa, Martin; Tichý, Lubomír; Willner, Wolfgang; Horsák, Michal
Abstract: Aim: Current species‐richness patterns are sometimes interpreted as a legacy of landscape history, but historical processes shaping the distribution of species during the Holocene are frequently omitted in biodiversity models. Here, we test their importance in modelling current species richness of vascular plants in forest and grassland vegetation. Location: Western Carpathians and adjacent regions. Taxon: Vascular plants. Methods: Numbers of all species and of habitat specialists were extracted from plot records of forest and grassland vegetation. For each plot, environmental and historical data were derived from thematic maps. Historical data related to the persistence of (a) temperate taxa during the Late Glacial and Early Holocene, (b) open‐landscape taxa during the Middle Holocene and (c) taiga taxa during the Late Holocene were based on 112 fossil pollen profiles. Boosted regression trees were used to model spatial patterns in species richness. Results: Historical variables always appeared among the best predictors of current species richness. In light forests, species richness highly mirrored both the Late Glacial (12.5% contribution) and Middle‐Holocene (8.6%) landscape history. The latter factor became an important predictor also for species richness of steppe grasslands (8.3%) along with temperature seasonality (11.9%). Species richness of dark coniferous forests was best predicted by the Late‐Holocene occurrence of taiga forests (14.8%), which had an even stronger effect on the richness of habitat specialists (20.5%). Main conclusions: Landscape changes since the Last Glacial Maximum are important predictors of current plant species richness. The historical effects were found to be habitat specific and, because they may interact with recent environmental conditions and anthropogenic pressures, they often show a nonlinear relationship with species richness. We provide one possible direction of incorporating past landscape changes to the models of species richness.